2014
DOI: 10.1038/eye.2014.233
|View full text |Cite
|
Sign up to set email alerts
|

Earlier therapeutic effects associated with high dose (2.0 mg) Ranibizumab for treatment of vascularized pigment epithelial detachments in age-related macular degeneration

Abstract: Summary statement Intravitreal high dose (2 mg) ranibizumab may lead to quicker resolution of choroidal neovascularization (CNV) and associated retinal pigment epithelial detachment in eyes with exudative age-related macular degeneration, although it may possibly correlate with RPE tears in certain cases. Purpose This prospective study compared the outcomes of 0.5 vs 2.0 mg intravitreal ranibizumab injections (RI) for treating vascularized pigment epithelial detachment (vPED) due to age-related macular degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
1
23
0
2
Order By: Relevance
“…Chan et al [43] recently reported results from a prospective study comparing the outcomes of 0.5 versus 2.0 mg intravitreal ranibizumab injections for treating vPED. The higher dose yielded more rapid reductions and more complete resolution of the PED; however, the incidence of RPE tear was higher in this group.…”
Section: Therapy In High-risk Patientsmentioning
confidence: 99%
“…Chan et al [43] recently reported results from a prospective study comparing the outcomes of 0.5 versus 2.0 mg intravitreal ranibizumab injections for treating vPED. The higher dose yielded more rapid reductions and more complete resolution of the PED; however, the incidence of RPE tear was higher in this group.…”
Section: Therapy In High-risk Patientsmentioning
confidence: 99%
“…; Chan et al. ). Our data indicate that there is a variable response to treatment, whereas overall there was a significant reduction in PED height.…”
Section: Discussionmentioning
confidence: 97%
“…During treatment, an individualized regime that is based on the patient's reaction is needed [19, 20]. For anti-VEGF drugs that have poor outcome, increasing the dosage, changing the drug, and combined treatment can be applied [21]. …”
Section: Discussionmentioning
confidence: 99%